2017
DOI: 10.1371/journal.pgen.1006918
|View full text |Cite|
|
Sign up to set email alerts
|

Kinesin-1 promotes chondrocyte maintenance during skeletal morphogenesis

Abstract: During skeletal morphogenesis diverse mechanisms are used to support bone formation. This can be seen in the bones that require a cartilage template for their development. In mammals the cartilage template is removed, but in zebrafish the cartilage template persists and the bone mineralizes around the cartilage scaffold. Remodeling of unmineralized cartilage occurs via planar cell polarity (PCP) mediated cell rearrangements that contribute to lengthening of elements; however, the mechanisms that maintain the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 88 publications
(136 reference statements)
3
19
1
Order By: Relevance
“…The efficiency of MO was evaluated by measuring the expression of clcn7 as assessed by Q-PCR and phenotypic penetrance. The injected embryos were cultured in the embryo medium and harvested at 3 dpf (days post-fertilization) or 5 dpf for the following experiments 28.…”
Section: Methodsmentioning
confidence: 99%
“…The efficiency of MO was evaluated by measuring the expression of clcn7 as assessed by Q-PCR and phenotypic penetrance. The injected embryos were cultured in the embryo medium and harvested at 3 dpf (days post-fertilization) or 5 dpf for the following experiments 28.…”
Section: Methodsmentioning
confidence: 99%
“…Together, these tools provide a more accurate way to measure autophagy activity and differences in autophagy levels quantitatively between different fish. Indeed, these tools have been used in zebrafish studies to determine how autophagic flux is affected by specific genetic mutations within bone and cartilage cells (Hu et al 2019 ; Santos-Ledo et al 2017 ). These studies showed that changes to bone and cartilage cell differentiation and functioning were in part due to dysregulated autophagy activity.…”
Section: Current Tools Available To Study Autophagy In Zebrafishmentioning
confidence: 99%
“…Invalidation of KIF5B in the mouse is embryonic lethal, although whether the mutant embryos presented with ciliopathy‐related phenotypes was not described [Tanaka et al ., ]. In Zebrafish, KIF5B isoforms were involved in cartilage remodelling and maintenance during craniofacial morphogenesis, but without an obvious connection to cilia‐related function [Santos‐Ledo et al ., ]. Loss of KLC1 in the mouse leads to brain specific defects which were not related to cilia [Rahman et al ., ].…”
Section: Pc‐specific Kifmentioning
confidence: 99%